Menyelaraskan Hubungan Gaya Pemimpin Pada Kondisi Pemberian Kompensasi Untuk Memaksimalkan Kinerja - Kurniawan Prambudi Utomo (Fakultas Ekonomi Universitas Islam 45, 2018)
PT Kresna Reksa Finance Jakarta can achieve its goals well if it runs the company according to its target by aligning its leadership style to performance-based compensation. The aim of this study is to determine whether the leader style when giving compensation can simultaneously improves company performance at PT Kresna Reksa Finance. Based on the research observations there are some problems that occur among some employees who feel their salary is low, also the allowances and bonuses are not appropriate, it needs serious management attentio. This study uses the personally administered questioneres method that is a face-to-face distribution questionnaire method to the respondent. This study illustrates that the value of leadership style towards compensation is in accordance with the performance that has been applied so that the company's target is exceeded. This can be seen from the equation of Y = 37,215 + 0.439X1 + 0.493X2 with the R-square of 0.78, which means that 78% of the independent variables of leadership style on the application of compensation are in accordance with performance and able to minimize the influence of other factors with a value of 22% other independent variables. The conclusion is that PT Kresna Reksa Finance Jakarta is appropriate and hopes to harmonize the relationship of leadership style, compensation, and performance of its employees